Research and implement on segmenting storage model of netflow - WU Guang-jun1; YUN Xiao-chun2; YU Xiang-zhan1; WANG Shu-peng2 (Tongxin xuebao)
A new model was proposed to maintain sequence and ownership of netflow.This model adopted weak se-quence-based high speed data structure in memory to improve real time storage ability.In the disc level a multi-level in-dex data netflow spanning tree was proposed to improve sequence and ownership retrieval efficiency.The performance of evaluation exposes that the storage model of netflow can improve real-time storage ability and decrease the quantities of index data dramatically.